Application Of Role Playing Method To Develop Linguistic Intelligence In Early Childhood In Paud West Banjarmasin - Nurilla Santi (Universitas muhammadiyah Banjarmasin, 2023)
This research aims to find out how the Application of Role Playing Methods To Develop Linguistic Intelligence in Early Childhood in Paud Banjarmasin Barat. The type of research used in this study is descriptive qualitative research. A natural object. Descriptive research is a study that gets a systematic, actual and accurate picture of the facts and development of individuals in school as it is. The object of his research is the application of role-playing methods. The data collection techniques used are observation, interview, documentation. Data analysis techniques are data reduction, data presentation and withdrawal of data validity test conclusions using test examination techniques using methods (trianggulation methods). Based on the results of research obtained that the results of the study showed that (Role Playing) To Develop Linguistic Intelligence in Early Childhood in Paud Banjarmasin Barat is still not fully developed children can not express, explore and experiment in developing various aspects of development.